EDUCATION DEVELOPMENT POLICY THROUGH SPECIAL AUTONOMY FUND AT THE DEPARTMENT OF EDUCATION AND CULTURE NORTH ACEH DISTRICT - Iryani, Lisa; Sufi, Sufi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study examines the policy of education development through special autonomy funds at the Education and Culture Office of North Aceh Regency. The research location is the Education and Culture Office of North Aceh Regency. The purpose of the study was to determine the policy of budgeting priorities in the education infrastructure development program and the program to improve the quality of educators and education personnel in North Aceh Regency and to determine the use of special autonomy funds in education infrastructure development programs in North Aceh Regency. The theoretical perspective used is the theory of public policy and the theory of educational development. The research method used is a qualitative research method. The results showed thatthe quality of education and physical development are not in line so that the results obtained are also not optimal, the lack of budget affects the improvement of the quality of educators and education personnel. Educational development in reality, especially the infrastructure development program has been able to run according to the program that has been prepared, and based on the budget for larger infrastructure development, it is still constrained by supporting facilities such as the construction of laboratories and teaching aids needed by schools that so far not sufficient.The obstacle to implementing the program to improve the quality of educators and education personnel lies in the limited budget. Thousands of teachers in North Aceh Regency need stages in the implementation of providing training and this cannot be completed in the annual budget.The allocation of a larger budget for infrastructure development is motivated by rationality, if the facilities and infrastructure can be adequate, it will support the process of improving the quality of education and be able to improve the quality of educators and education personnel